A theater for the pandemic: alternatives to the performing arts in the time of coronavirus in Peru, and the Teatro Británico’s virtual project «Unfiltered» - Barraza Eléspuru, Ernesto (2020)
This article focuses its analysis on the «Sin Filtro» [«Unfiltered»] project, launched by Lima’s Teatro Británico, in response to the crisis in Peru’s performing arts sector in the context of the state of emergency caused by the Covid-19 outbreak. The state of emergency began on March 16th 2020, and at the time of writing remained in place. The subjects of this article’s analysis are the four plays written and produced as part of the as part of the first stage of the project. The text reflects upon, describes and analyzes the factors underpinning a new creative process, embodied by the aforementioned project, while exploring to what extent the performing arts are possible when expressed through a virtual medium, in response to a context that has forced the closure of theaters throughout the world and created mass unemployment within the sector.